STRUCTURAL ANALYSIS OF IT TERMINOLOGY: MORPHOLOGICAL, SEMANTIC AND WORD-FORMATION PROCESSES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the structural composition of IT terminology through morphological, semantic, and word-formation analysis. It focuses on how English and Russian IT terms are formed using compounding, affixation, conversion, abbreviations, metaphorical extension, semantic narrowing, and the creation of new international neologisms. The study highlights the dynamic nature of IT vocabulary and its rapid development driven by technological innovation and global digitalization. The findings demonstrate that IT terminology represents one of the most rapidly expanding layers of modern technical language.